A autonomia de docentes de enfermagem na (co)construção da competência clínica - Campos, Leonara Raddai Gunther de (2019)
Acting as a teacher in clinical nursing education requires clinical competence (CC) to facilitate student learning. Considering the relevance of this assertion and the studies by Benner (1984), we assume that the development of clinical competence is facilitated by the acquisition of clinical experiences prior to the teaching career, and its consequent evolution is conditioned to the teacher’s continuous contact with real practice scenarios, and the use of strategies that favor career improvement. Thus, the research question arose: How do nursing teachers develop clinical competence for the teaching of nursing care? In order to analyze the complexity that permeates the process of development of clinical competence, this qualitative study uses, throughout its development, complex thinking and bricolage as a theoretical and methodological referential. Research developed at the Federal University of Mato Grosso - UFMT, with participation of effective and substitutes nurse teachers from nursing courses in Cuiabá campuses; Rondonópolis; Sinop and Araguaia. The strategies of data production included the following levels of approximation with the object: Literature integrative review conducted in 2017; Application of a closed questionnaire about the professional life of participants before and after teaching at UFMT in 2018; Semi-structured interviews with 8 managers and 14 teachers from Cuiabá and Araguaia campuses, carried out from September 2018 to February 2019. Analysis developed simultaneously to the production of data, found out at the end, and followed a handcrafted path composing the phases: Objet Trouvé; Decoupage and Inforgraphics. The results stand out in the first level of approximation with the object that the nursing teacher has universal purpose in Clinical Teaching, together with the (co) responsibility for the development of the student's CC. Besides being the main articulating axis between teaching and service, they feel responsible for the maintenance of clinical and insecure regarding to their practical performance. The second level shows that teachers, most of the times, come from public schools, a large portion had the opportunity to participate in programs of Scientific Initiation, and had as their first job in nursing the hospital care activity, followed by teaching after graduating. They use diversified training strategies to develop their CC throughout their careers; however, the theoretical format is prioritized. They sought and still seek in the broad and stricto-sensu postgraduate, ways to develop their CC both before and after teaching in that institution. The third level presents that the notion of shared CC follows the paradigmatic transition process, and for this, they consider very important the clinical experience prior to the teaching career, however, not defining. Although little considered in the processes of teacher recruitment and burden distribution, CC is intrinsically linked to the processes of development of teachers’ autonomy and self-ethics, which may, from their pro-activity, seek the continuous development of their CC throughout their career, even with the institution not making specific policies available for this purpose. It is concluded that the theme is complex and opens possibilities for further discussions on institutional policies.